Pemisahan Cerium dari Logam Tanah Jarang Hidroksida Melalui Kalsinasi dan Pelindian Menggunakan HNO3 Encer - Trinopiawan, Kurnia; Purwani, Maria Veronica; Anggraini, Mutia; Prassanti, Riesna (EKSPLORIUM, 2019)
Application of Rare Earth Elements (REE) uses broadly in various fields related to modernization. It causes many companies are developing processing techniques to extract REE from rare earth mineral deposits. REE hydroxide processing into cerium oxide, lanthanum oxide, and neodymium concentrates has conducted by PSTA-BATAN in collaboration with PTBGN-BATAN. The previous economic study issued in excessive ammonia caused by the use of concentrated nitric acid in the cerium dissolution process. Therefore, process innovation is necessary to do by calcination and leaching methods using dilute HNO3. This research aims to determine the effectiveness of the calcination and leaching process with dilute HNO3. Calcination conducted at 1000°C temperatures with the observing parameters is calcination time, HNO3 concentration, and leaching rate. The result of the study is that calcination can convert REE hydroxide into REE oxide. The longer calcination time, the easier the REE oxide formed. The three hours calcination process enhances the concentration of La, Ce, and Nd from 7.80%, 28.00%, and 15.11% to 12.69%, 45.50%, and 24.45% respectively. The kinetic reaction of the RE(OH)3 calcination reaction follows a chemical reaction process with the equation y = 0.3145x + 0.0789 and R2 = 0.9497. Then, REE oxide from calcination reacted with dilute HNO3. The higher the concentration of HNO3 at various leaching levels, the better the leaching efficiency of La and Nd while Ce is impossible to leach or the leaching efficiency is close to zero. The optimum leaching process on three levels of leaching conditions is using 1 M HNO3. The leach reaction kinetics follows the core shrinkage model of the surface chemical reaction with the equation y = 0.1732x - 0.2088 and R2 = 0.9828.